ANALISIS PENERIMAAN PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR DI KABUPATEN MINAHASA SELATAN - Karim, Fikram Pratama A.; Alexander, Stanly W.; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2018)
To fulfill the interests of the people, where the need for these funds increases every year along with the increase in population and the needs of the people. The funds that will be spent on this development are certainly obtained from the people themselves through a collection called tax. The purpose of this study was to determine motor vehicle tax revenue and the transfer fee of motor vehicle names in the South Minahasa regency and what obstacles / efforts were made by the government to increase tax revenues. The analytical method used in this study is a qualitative method with descriptive data analysis techniques. The results showed that the procedures for calculating PKB and BBNKB of South Minahasa Samsat UPTD had followedÂ local regulation No.7 of 2011, and PKB collection for each year for collection of BBNKB. Keywords: Motor vehicle reception tax, duty of transferringÂ name of a motor vehicle